Analisis Likuiditas, Solvabilitas, Profitabilitas Sebelum dan Saat Covid-19 Terhadap Return Saham pada Perusahaan Real Estate and Property yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2021 - Nova Gita Regina; Rina Asmeri; Delori Nancy Meyla (Ekasakti Matua Jurnal Manajemen, 2024)
This study aims to examine and analyze the influence of liquidity, solvency and profitability before and after Covid-19 on stock returns in real estate and property companies listed on the Indonesia Stock Exchange. The population of this study are 54 real estate and property companies listed on the Indonesia Stock Exchange and a sample of 10 real estate and property companies listed on the Indonesia Stock Exchange. This study uses the classical assumption test, heroscadicity test and different test. The results of the research on liquidity did not have a significant effect before Covid-19 with a significant value of 0.338 on stock returns in real estate and property companies listed on the Indonesia Stock Exchange and liquidity during Covid-19 had no effect with a significant value of 0.273 on stock returns in real estate and property companies listed on the Indonesia Stock Exchange, solvency had a significant effect before with a significant value of 0.001 and during Covid-19 it was not significant with a significant value of 0.184 on stock returns in real estate and property companies listed on the Indonesia Stock Exchange and profitability had a significant effect before Covid-19 with a significant value of 0.001 on stock returns in real estate and property companies listed on the Indonesia Stock Exchange and profitability has a significant effect with a significant value of 0.000 on stock returns in real estate and property companies listed on the Indonesia Stock Exchange.